L’aqueduc du Gier : nouvelles données sur le pont-siphon de Beaunant à Sainte-Foy-lès-Lyon (Métropole de Lyon) - David Baldassari; François Blondel; Stéphane Gaillot (Gallia)
In 2018, an archaeological excavation was undertaken to study three piers (17, 18 and 19) of the Yzeron aqueduct at Beaunant (Sainte-Foy-lès-Lyon, France) which supported the conduits of a siphon that carried water from the Gier aqueduct to Lugdunum in Antiquity.The Yzeron siphon, which covered a length of 2,660 m and was located less than 20 km from the source of the Gier aqueduct on Fourvière hill in Lyon, made it possible to cross the Yzeron Valley which, at this point, was almost 1.50 km wide and 125 m deep. The remarkably well-preserved aqueduct first featured in the inventory of Historical Monuments in 1875. Its deck was 290 m long at the deck, it stood 18 m high at its central part and had 30 arches supported by 29 piers. Fifteen arches remain today.The excavation, motivated by the improvement in the state of the river, revealed the opus quadratum foundations at the base of two piers (17 and 19) and uncovered the well-preserved remains of a wooden frame used to carry out the opus caementicium for the foundation block of pier 18.On the right bank of the river, this operation made it possible, against all odds, to bring to light the foundation block of pier 17, whose 38° tilt easterly testifies to the violence of the bridge collapse. The start of its rising section was found nearby in a secondary position in the form of a large fragment of masonry over 5 m long. Several large-scale limestone blocks were found, either associated with this fragment or in close proximity, suggesting that pier 17 was elevated from an opus quadratum base.On the left bank of the Yzeron, preserved to a height of nearly 6 m, pier 19 was visible to the base of its elevated section. However, care had to be exercised respecting the strength of this pier, which limited archaeological exploration to two trenches located to the north and south below the level of the first opus reticulatum revealed by the removal of the topsoil. Nonetheless, these two trenches revealed a base consisting of three courses of large limestone blocks measuring up to 2 m in height.The opus quadratum foundations of these two piers were built using limestone blocks originating from regional quarries. One type was oolitic Bathonian limestone from Beaujolais (Lucenay stone), the outcrops of which are located in the Beaujolais hills on the right bank of the Saône, about 20 km as the crow flies north of the site. The other type was Portlandian limestone from Bugey (choin de Fay), whose outcrops are located on either side of the course of the Upper Rhône in the departments of Ain and Isère, 60 km away, east of Lyon. These blocks, averaging some 1.20 m in length and between 0.40 and 0.70 m in thickness, were assembled with live joints and secured with metal clamps sealed with lead in holes drilled into their base.The foundation block of pier 18, preserved in the middle of riverbed, was examined by means of a deep test trench dug on the south side, which revealed a pinewood foundation frame which reached down to the base of the masonry at a depth of 3.44 m. The frame consisted of square and rectangular section posts 0.13 to 0.15 m wide and planks 0.36 m wide and 25 mm thick, sometimes fixed roughly to the posts with iron nails. Dendrochronological analyses revealed that the trees from which the planks were taken were felled in 110 AD, indicating that the construction of the Gier aqueduct took place early in the 2nd century AD at the end of the reign of Emperor Trajan. The excavation also revealed the presence of a large opus caementicium base between piers 18 and 19. The presence of this masonry structure suggests that in Antiquity the main channels of the river probably passed between the piers at the bottom of the eastern slope of the valley.Beyond this indication of the old route of the river, the geoarchaeological approach also provides matter for discussion on the possible causes of the collapse of the bridge, which probably involved one or more consecutive or associated factors: weaknesses in the subsoil, the influence of meteorological factors or natural disasters.The data acquired during this excavation contribute significantly to ideas about the techniques and architectural choices that governed the construction of the bridge, together with more general thinking about the dating of a hydraulic structure as important as the Gier aqueduct, which is of not insignificant impact for the analysis of the urban development of the Roman colony of Lugdunum.